Priority and synonymy of some North American cicada genera (Hemiptera: Cicadidae: Cicadinae: Cryptotympanini) - Sanborn, Allen F.; Heath, Maxine S. (Zootaxa, 2017)
The status of several North American cicada genera is reconsidered based on the recent erection of new genera and historical evidence. Megatibicen Sanborn & Heath, 2016 is shown to have priority over Megatibicen Lee, 2016 (which was changed by the author to Gigatibicen Lee, 2016 prior to formal publication). Ameritibicen Lee, 2016 is shown to be a junior synonym of Megatibicen Sanborn & Heath, 2016 and both Ameritibicen n. syn. and and Gigatibicen Lee, 2016 n. syn. are synonymized here to Megatibicen Sanborn & Heath. The species placed in Gigatibicen are returned to Megatibicen to become Megatibicen auletes (Germar, 1834) n. comb., Megatibicen resh (Haldeman, 1852) n. comb., and Megatibicen resonans (Walker, 1850) n. comb. while the species placed in Ameritibicen remain in Megatibicen due to the junior synonym status of Ameritibicen. The monospecific Paratibicen Lee, 2016 n. syn. is shown to be a junior synonym of Neotibicen Hill & Marshall, 2015 and its species is reassigned to Neotibicen to become Neotibicen similaris (Smith & Grossbeck, 1907) n. comb.